2012
DOI: 10.1007/s00411-011-0400-y
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia incidence in the Russian cohort of Chernobyl emergency workers

Abstract: Of all potentially radiogenic cancers, leukemia, a type of cancer of the blood, has the highest risk attributable to ionizing radiation. Despite this, the quantitative estimation of radiation risk of a leukemia demands studying very large exposed cohorts, because of the very low level of this disease in unexposed populations and because of the tendency for its radiation risk to decrease with time. At present, the Japanese cohort of atomic bomb survivors is still the primary source of data that allows analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 10 publications
1
35
1
Order By: Relevance
“…In fact, a number of authors have predicted and reported the increased incidence of leukemia among clean-up workers in Russia, Belarus and Ukraine. According to Ivanov et al, the dynamics of standardized incidence ratio demonstrates a 2.5-3-fold increase in the leukemia incidence in Russian cohort of Chernobyl clean-up workers in 5-7 years after the accident [7] . Prisyazhniuk et al stated statistically significant increment in observed-to-predicted ratio of leukemia and lymphoma incidence: 2.6 in 1990-1993 and 2.0 in 1994-1997 [8] .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a number of authors have predicted and reported the increased incidence of leukemia among clean-up workers in Russia, Belarus and Ukraine. According to Ivanov et al, the dynamics of standardized incidence ratio demonstrates a 2.5-3-fold increase in the leukemia incidence in Russian cohort of Chernobyl clean-up workers in 5-7 years after the accident [7] . Prisyazhniuk et al stated statistically significant increment in observed-to-predicted ratio of leukemia and lymphoma incidence: 2.6 in 1990-1993 and 2.0 in 1994-1997 [8] .…”
Section: Introductionmentioning
confidence: 99%
“…76 As noted in the preceding section, a history of radiation therapy-either alone or in combination with chemotherapy for prior neoplastic or nonneoplastic conditions-is recognized as being associated with an increased risk for AL, particularly AML. Radiation exposure for individuals near natural disasters or atomic bomb explosions is also associated with an increased risk of leukemia, 77,78 and reportedly, radiation exposure after diagnostic procedures, including computed tomography scans in children, increases the risk for leukemia. 79,80 Patients receiving hematopoietic stem cell therapy are at increased risk for development of MDS and AML.…”
Section: Strong Recommendationmentioning
confidence: 99%
“…[81][82][83] The incidence appears to be increased in older patients and in patients who received total-body radiation. 78 Exposure to certain chemicals is associated with an increased risk of development of AL, particularly AML. Benzene exposure, especially at high levels, is associated with an increased risk of AML.…”
Section: Strong Recommendationmentioning
confidence: 99%
“…Considering the above, the studies (Ivanov et al 2012;Zablotska et al 2013) provide no conclusive evidence of an incidence increase of leukemia due to ionizing radiation after the Chernobyl accident. At the same time, such reports give rise to the statements in some reviews about "a two-fold increase in the incidence of leukemia between 1986 and 1996 in Russian emergency and recovery operation workers exposed to external dose of more than 150 mGy" (Balonov 2013), which is not in agreement with the above-cited conclusions by the UNSCEAR (2000,2008).…”
mentioning
confidence: 97%
“…Furthermore, Ivanov et al (2003Ivanov et al ( , 2012 used the "age-specific Russian male population rates" for an external comparison (Ivanov et al 2003). The counterpart of the liquidators in the population -middle-aged men -have generally not been covered by medical examinations; their access to modern health care has been limited (Jargin 2013).…”
mentioning
confidence: 99%